Prioritizing hospital for managing construction protecting against man made threat - Hassan Piri; Hamed Hassan nejad; Mahdi Akbar Fakhrabadi (مهندسی و مدیریت ساخت)
Due to the existence of dangerous areas that are likely to present the nationality, independence and territorial integrity of the country, the need to pay attention to inactive abilities is a priority. This is an important and urgent contribution that requires medium and long-term planning to be carried out by relevant centers. Rehabilitation of buildings, in particular service buildings - a therapy that plays an essential role in establishing the people's psychological and psychological well-being of the people against accidents during acts of fear of the enemy and the occurrence of a crisis. Hence, the importance of rehabilitating hospitals to reduce their vulnerability to probable probabilties is not uncovered today, so reforming centers like health centers is indispensable and indisputable. Obviously, the rehabilitation of several hospitals at the same time is unreasonable and precludes the accuracy and accuracy of the work, so their priority must be made in a proper and appropriate manner so that it can be upgraded. In this research, a model based on the prioritization of hospitals to promote them is presented. In this model, the priority assessment of hospitals is based on the number of classes, the quality of the structural score, the amount of space consumed, the relative risk of the earthquake, the year of construction and operation, and the weights of these indicators based on explosion resistance criteria, operational capability , Performance continuity, productivity, reliability, and flexibility in upgrading.